2004
DOI: 10.1111/j.1462-5822.2004.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the mechanisms of Salmonella-induced actin assembly during invasion of host cells and intracellular replication

Abstract: SummarySalmonella enterica serovar Typhimurium ( S. typhimurium ) induces actin assembly both during invasion of host cells and during the course of intracellular bacterial replication. In this study, we investigated the involvement in these processes of host cell signalling pathways that are frequently utilized by bacterial pathogens to manipulate the eukaryotic actin cytoskeleton. We confirmed that Cdc42, Rac, and Arp3 are involved in S. typhimurium invasion of HeLa cells, and found that N-WASP and Scar/WAVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 64 publications
3
90
0
3
Order By: Relevance
“…Recent data suggested that WAVE complex induces ruffling but is dispensable for efficient entry, whereas a novel Arp2/3 complex activator, WASH, mediates entry [36]. Activation of the Arp2/3 complex, which initiates actin nucleation and branching, results in membrane ruffling and/or bacterial uptake depending on the Arp2/3 complex activator [37]. Hence, regulation of Rac-and Cdc42-mediated signaling events seems to be crucial for Salmonella to successfully establish infection through a Zipper and a Trigger entry process.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggested that WAVE complex induces ruffling but is dispensable for efficient entry, whereas a novel Arp2/3 complex activator, WASH, mediates entry [36]. Activation of the Arp2/3 complex, which initiates actin nucleation and branching, results in membrane ruffling and/or bacterial uptake depending on the Arp2/3 complex activator [37]. Hence, regulation of Rac-and Cdc42-mediated signaling events seems to be crucial for Salmonella to successfully establish infection through a Zipper and a Trigger entry process.…”
Section: Discussionmentioning
confidence: 99%
“…Cortactin is necessary for S. flexneri entry into host cells, but is not required by S. enterica (58,59). Hyperacetylation of lysine residues within cortactin in the absence of HDAC6 activity can interfere with the ability of cortactin to bind F-actin (57), and this may account for the inhibitory effect of TSA on host cell invasion by S. flexneri, but not S. enterica.…”
Section: Microtubules Are Required For Upec Invasion Of Host Cells-mentioning
confidence: 99%
“…Further studies will be needed to fully understand the mechanism of the manipulation of actin through SteC-host protein interactions. The data presented here provide the missing link between SteC and actin manipulation, explaining how SteC's effects can be independent of the well known route to actin remodeling through Cdc42, Rac, N-WASP, Scar/WAVE, and Arp2/3, which are common targets of pathogens (10). Thus, the phosphorylation of HSP27 represents a novel mechanism for pathogen-induced manipulation of the actin cytoskeleton.…”
Section: Fig 2 Host Cell-specific Modulation Of Cellular Processes mentioning
confidence: 74%
“…SteC has been identified as the sole serine/threonine protein kinase encoded in the Salmonella genome (8), but the target substrates of this kinase within the host are not fully understood, although it has been demonstrated that SteC partially targets the MAP kinase MEK (9). Interestingly, SteC is capable of promoting assembly of an F-actin meshwork around the SCV; this is dependent on its kinase activity but does not require activation of signaling pathways through Rho-associated protein kinase (8), Cdc42, Rac, N-WASP, Scar/WAVE, and Arp2/3 (10). These host signaling proteins are the main targets of T3SS-secreted effectors from many pathogens, including the SPI1 system in Salmonella (11) and Shigella (12).…”
mentioning
confidence: 99%